Dealing with apparatus in laboratory: science teachers' perception and practices - Kamarudin, Nurzatulshima (Human Resource Management Academic Research Society, 2018)
The use of laboratory is centered on students’ involvement in solving problems related to science concepts. For troubleshooting purposes, appropriate apparatus will be used, namely laboratory apparatus, chemicals, specimens, and so on. The correct and appropriate interaction between students and laboratory apparatus can lead to critical, creative and analytical thinking. The planning and handling of laboratory apparatus for practical activities need to be carried out carefully so that the learning outcomes of these activities can be obtained effectively. This working paper aims to shed light on the results of the study on science teachers who employ laboratory. The focus of the study is on the management of apparatus during practical classes conducted. A total of five science teachers were selected through purposive sampling from the Central Zone. Observation instruments and open questionnaire were used in this study while the data were analyzed manually based on themes relevant to the question of this research. The results showed that all science teachers prepared practical apparatus before students’ arrival to the laboratory. They also provided practical manual to guide the students, especially regarding practical apparatus and laboratory procedures. The results of the open-ended questionnaire analysis showed that all the teachers complained of the lack of apparatus when it comes to certain practical. They also stressed the need for the presence of laboratory assistants in helping to manage practical classes, especially from the aspect of apparatus management. The study concluded that a list of practical science apparatus management proposals be put forward to improve the implementation of practical methods by Science teachers.